DNA thermo-protection facilitates whole genome sequencing of Mycobacteria direct from clinical samples - George, S; Xu, Y; Rodger, G; Morgan, M; Sanderson, N; Hoosdally, SJ; Thulborn, S; Robinson, E; Rathod, P; Walker, AS; Peto, TEA; Crook, DW; et al. (American Society for Microbiology, 2020)
Mycobacterium tuberculosis (MTB) is the leading cause of death from bacterial infection. Improved rapid diagnosis and antimicrobial resistance determination, such as by whole genome sequencing, are required. Our aim was to develop a simple, low-cost method of preparing DNA for sequencing direct from MTB positive clinical samples (without culture). Simultaneous sputum liquefaction, bacteria heat-inactivation (99°C/30min) and enrichment for Mycobacteria DNA was achieved using an equal volume of thermo-protection buffer (4M KCl, 0.05M HEPES buffer pH7.5, 0.1% DTT). The buffer emulated intracellular conditions found in hyperthermophiles, thus protecting DNA from rapid thermo-degradation, which renders it a poor template for sequencing. Initial validation experiments employed Mycobacteria DNA, either extracted or intracellular. Next, mock clinical samples (infection-negative human sputum spiked 0-105 BCG cells/ml) underwent liquefaction in thermo-protection buffer and heat-inactivation. DNA was extracted and sequenced. Human DNA degraded faster than Mycobacteria DNA, resulting in target enrichment. Four replicate experiments achieved MTB detection at 101 BCG cells/ml, with 31-59 MTB complex reads. Maximal genome coverage (>97% at 5x-depth) occurred at 104 BCG cells/ml; >91% coverage (1x depth) at 103 BCG cells/ml. Final validation employed MTB positive clinical samples (n=20), revealing initial sample volumes ≥1ml typically yielded higher mean depth of MTB genome coverage, the overall range 0.55-81.02. A mean depth of 3 gave >96% one-fold TB genome coverage (in 15/20 clinical samples). A mean depth of 15 achieved >99% five-fold genome coverage (in 9/20 clinical samples). In summary, direct-from-sample sequencing of MTB genomes was facilitated by a low cost thermo-protection buffer.